2011
DOI: 10.1038/ajg.2011.72
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic Therapy in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: The etiology of inflammatory bowel disease (IBD) is unknown but may relate to an unidentified bacterial pathogen or an immunological reaction to gut microbiota. Antibiotics have therefore been proposed as a therapy for Crohn's disease (CD) and ulcerative colitis (UC) to induce remission in active disease to prevent relapse. Current data are conflicting and we therefore conducted a systematic review of randomized controlled trials (RCTs) evaluating antibiotics in IBD. Only parallel group RCTs were considered el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
342
1
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(365 citation statements)
references
References 48 publications
7
342
1
15
Order By: Relevance
“…Our study echoed the observed trends that more IM but less 5-ASA products are currently used in CD management [18][19][20][21][22] . Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] . A recent meta-analysis showed a combined pooled HR of 0.59 for first intestinal resection with thiopurine use [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study echoed the observed trends that more IM but less 5-ASA products are currently used in CD management [18][19][20][21][22] . Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] . A recent meta-analysis showed a combined pooled HR of 0.59 for first intestinal resection with thiopurine use [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Metronidazole, in combination with azathioprine, has also shown efficacy in reducing postoperative occurrence of CD [124]. A meta-analysis of antibiotic therapy in IBD found that antibiotics significantly improved outcomes [125]. However, this analysis included patients who were treated with a diverse number of antibiotics.…”
Section: Therapeutic Manipulationmentioning
confidence: 99%
“…( 65 ). A recent meta-analysis supports a role for antibiotics in induction of remission of Crohn ' s disease, UC, and perianal fi stulae, although the authors noted marked diversity in treatment design and heterogeneity in outcomes ( 66 ). Th is analysis was fl awed by inclusion of anti-tuberculous treatment of Crohn ' s disease, which is not standard practice.…”
Section: Therapeutic Approachesmentioning
confidence: 99%